Importance of IL-10 Modulation by Probiotic Microorganisms in Gastrointestinal Inflammatory Diseases - de Moreno, Maria Alejandra (2011)
Lactic acid bacteria (LAB) represent a heterogeneous group of microorganisms that are naturally present in many foods and possess a wide range of therapeutic properties. The aim of this paper is to present an overview of the current expanding knowledge of one of the mechanisms by which LAB and other probiotic microorganisms participate in the prevention and treatment of gastrointestinal inflammatory disease through their immune-modulating properties. A special emphasis will be placed on the critical role of the anti-inflammatory cytokine IL-10, and a brief overview of the uses of genetically engineered LAB that produce this important immune response mediator will also be discussed. Thus, this paper will demonstrate the critical role that IL-10 plays in gastrointestinal inflammatory diseases and how probiotics could be used in their treatment.